2018
DOI: 10.1515/ijnes-2016-0063
|View full text |Cite
|
Sign up to set email alerts
|

Status of Violence in a Selected Faculty: The Students’ Experience

Abstract: The present study is aimed at examining the status of violence among the students of nursing, midwifery, and operating room. A self-reporting questionnaire with two sections of demographic characteristics and experience of violence was used. The data obtained were analyzed, using SPSS software. 58.7 percent of the students had a history of violence in the previous year. The maximum percentage of violence exposure belonged to the students of operating room (76.9%). The highest incidence of violence was verbal (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…If incidents are not reported they may not be dealt with and it becomes difficult to identify particular hotspots for aggression. There is some limited evidence that student nurses do not report incidents (Tee et al, 2016), in part because students do not see any outcome to the reporting (Fathi et al, 2018). Understanding the reasons for underreporting will enable solutions to be created that address the specific barriers identified by students.…”
Section: Introductionmentioning
confidence: 99%
“…If incidents are not reported they may not be dealt with and it becomes difficult to identify particular hotspots for aggression. There is some limited evidence that student nurses do not report incidents (Tee et al, 2016), in part because students do not see any outcome to the reporting (Fathi et al, 2018). Understanding the reasons for underreporting will enable solutions to be created that address the specific barriers identified by students.…”
Section: Introductionmentioning
confidence: 99%
“…Scherer, Scherer, Rossi, Vedana, and Cavalin (2015) report similar findings amongst Brazilian student nurses (Scherer et al, 2015). In another study in the US, over 50% of the undergraduate nursing students reported experiencing or witnessing horizontal violence at least once in the clinical setting (Wallace & Tucker, 2019), whilst 37.3% of nursing students in Hong Kong reported having experienced clinical violence during their nursing studies (Cheung, Ching, Cheng, & Ho, 2019) and 55.2% of Iranian nursing students experienced violence in the previous academic year (Fathi et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…It is disheartening to realize "eating our young" (Meissner, 1986) begins early in nursing education and persists in the profession. This phenomenon also occurs in other countries, for example, Fathi et al (2018) reported that nursing students experienced verbal violence in Iran. This begs the question of whether incivility has become a ritualistic part of the nursing culture.…”
Section: Discussionmentioning
confidence: 64%